(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the use of digital technologies in the publishing industry in foreign countries. The research focuses on key digital technologies such as e-books, digital journals, interactive publications, as well as the role of artificial intelligence (AI) and cloud storage. The article provides information on how traditional publishing methods are being transformed and how new opportunities for growth, efficiency, and audience expansion are being created. Additionally, it discusses the development of online publishing platforms and the impact of digital marketing strategies, such as social media and email marketing, on the global distribution of publications. The study emphasizes the significant impact of digital technologies on the publishing industry, helping to enhance adaptability and competitiveness on a global scale.